From early child development to human development : investing in our children's future - Young, Mary E., 1955-; World Bank. (Washington, D.C. : World Bank, 2002)
"Children are our future. Investing in every child at an early age is an investment in human and economic development for all. Children born in poverty are far more likely to grow up stunted in both body and mind. Science tells us that early child development is critical and marks a child for life. Young children who are well nurtured do better in school and can develop the skills to compete in a global economy. Recently, the World Bank hosted a conference to review the state of knowledge on brain development, the link between early child development (ECD) and human development, standards of care to improve children's educatinoal outcomes, qualitative and quantitative measures of effective programs, and elements of quality in ECD programs. The world's leading experts from non-governmental, governmental, multilateral and bilateral organizations urged the public and private sectors to enhance and coordinate activities and to formulate policies to advance the development of all children and to "narrow the gap" for poor children. This book contains essential resource information that includes descriptions and case studies of successful ECD programs throughout the world. Written in an accessible style, it is invaluable for all policymakers and practitioners concerned about human development and education of children worldwide" -- BOOK JACKET.
1. Introduction and overview / Mary Eming Young -- 2. Early child development and the brain: the base for health, learning, and behavior throughout life / J. Fraser Mustard -- 3. From child development to human development / Jacques van der Gaag -- 4. Standards of care: investments to improve children's educational outcomes in Latin America / J. Douglas Willms -- 5. Ensuring a fair start for all children: the case of Brazil / Mary Eming Young -- 6. Investing in effective childcare and education: lessons from research / John M. Love, Peter Z. Schochet and Alicia L. Meckstroth -- 7. Mapping and documenting effective programming / Judith L. Evans -- 8. Effective early childhood programs: the U.S. Head Start experience / Louisa B. Tarullo -- 9. Elements of quality in home visiting programs: three Jamaican models / Kerida Scott-McDonald -- 10. Role of the private sector in early child development / Robert G. Myers -- 11. Communities can make a difference: five cases across continents / Simone Kirpal -- 12. Narrowing the gap for poor children / Enrique V. Iglesias and Donna E. Shalala -- 13. The political challenge: commitment and cooperation / Eduardo A. Doryan, Kul C. Gautam and William H. Foege.ssible styl
"Proceedings of a World Bank conference ... Washington, D.C., April 10-11, 2000"--Verso t.p.
Includes bibliographical references and index.
Keywords: Child development -- Congresses; Child health services -- Congresses; Early childhood education -- Congresses